2020
DOI: 10.1007/s13726-020-00859-9
|View full text |Cite
|
Sign up to set email alerts
|

Rubber compounds made of reactivated EPDM for fiber-reinforced elastomeric isolators: an experimental study

Abstract: Rubber recycling technology is a popular issue in many research fields, considering the huge amount of rubber waste in the environment. This paper discusses an application of regenerated ethylene propylene diene monomer (EPDM) to produce vulcanized items such as fiber-reinforced elastomeric isolators (FREIs), which are nowadays considered efficient low-cost seismic protection devices for low rise buildings (e.g., made by masonry) in developing countries. Two types of regenerated EPDM are studies and blended wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This type of rubber compound, made of natural rubber (NR), guarantees a good performance in terms of energy dissipation (Figure 1), but at the same time, it is vulnerable to quick aging. To protect the HDR, it has been considered a second rubber compound used as ring for each pad, namely a reactivated EPDM made with 2/3 of regenerated rubber and 1/3 of virgin rubber [8,9,10] which shows good performances even under aging effects (Figure 2). In Figure 3 it's possible to see the single rubber pad, made of an EPDM frame (Green) with a thickness of 5 mm, and the core (65x65 mm 2 ) of HDR (Red).…”
Section: Rubber Mechanical Propertiesmentioning
confidence: 99%
“…This type of rubber compound, made of natural rubber (NR), guarantees a good performance in terms of energy dissipation (Figure 1), but at the same time, it is vulnerable to quick aging. To protect the HDR, it has been considered a second rubber compound used as ring for each pad, namely a reactivated EPDM made with 2/3 of regenerated rubber and 1/3 of virgin rubber [8,9,10] which shows good performances even under aging effects (Figure 2). In Figure 3 it's possible to see the single rubber pad, made of an EPDM frame (Green) with a thickness of 5 mm, and the core (65x65 mm 2 ) of HDR (Red).…”
Section: Rubber Mechanical Propertiesmentioning
confidence: 99%
“…Another strategy for rubber wastes recycling is by blending the vulcanized rubbers with the virgin materials 6 . Habieb et al reported the possibility producing recycled rubber in the form of reactivated ethylene propylene diene monomer (EPDM) made by 2/3 of regenerated rubber and 1/3 of virgin rubber for the production of low cost rubber isolators 7 . Further investigation on reinforcement of the EPDM rubber blend with glass fiber was reported by Pianese et al 8 However, the potential application of materials produced by this technique is limited due to poor interfacial adhesion between recycled rubbers and virgin materials in which significantly reduces performance of the final products.…”
Section: Introductionmentioning
confidence: 99%
“…6 Habieb et al reported the possibility producing recycled rubber in the form of reactivated ethylene propylene diene monomer (EPDM) made by 2/3 of regenerated rubber and 1/3 of virgin rubber for the production of low cost rubber isolators. 7 Further investigation on reinforcement of the EPDM rubber blend with glass fiber was reported by Pianese et al 8 However, the potential application of materials produced by this technique is limited due to poor interfacial adhesion between recycled rubbers and virgin materials in which significantly reduces performance of the final products. Therefore, a feasible technology is required to fabricate more sustainable rubber, which is in conjunction with Sustainable Development Goal 12 to ensure efficient use of natural resources as well as reducing waste generation through prevention, reduction, recycling and reuse.…”
Section: Introductionmentioning
confidence: 99%
“…A new composition is developed basing on the past experience of the re-search group and in particular with reference to a previous study by A. B. Habieb et al [12,13].…”
Section: Introductionmentioning
confidence: 99%